Minyoo Matata - The vicious worm - A Taenia solium computer-based health-education tool - in Swahili - Trevisan, C.; Fèvre, Eric M.; Owiny, M.; Ngere, I.; Johansen, M.V. (Elsevier, 2017)
Lack of knowledge is one of the main risk factors for the spread of the zoonotic parasite Taenia solium. The computer-based health-education tool 'The Vicious Worm' was developed to create awareness and provide evidence-based health education as a specific measure in control strategies. To increase the reach of the tool, a new version in Swahili was developed and can now be downloaded for free from http://theviciousworm.sites.ku.dk.